2020
DOI: 10.3390/v12070744
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of the Human Papillomavirus Life Cycle by DNA Damage Repair Pathways and Epigenetic Factors

Abstract: Human papillomaviruses are the causative agents of cervical and other anogenital cancers along with approximately 60% of oropharyngeal cancers. These small double-stranded DNA viruses infect stratified epithelia and link their productive life cycles to differentiation. HPV proteins target cellular factors, such as those involved in DNA damage repair, as well as epigenetic control of host and viral transcription to regulate the productive life cycle. HPVs constitutively activate the ATM and ATR DNA repair pathw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
26
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(28 citation statements)
references
References 89 publications
0
26
0
2
Order By: Relevance
“…In addition, the stress caused by viral replication often establishes a high NAD + -state that activates SIRTs [ 128 , 132 ]. Another approach can be based on the transcriptional functions of certain SIRTs that appear necessary for the regulation of viral gene expression [ 120 , 121 , 134 , 135 ]. Therefore, fine-tuning of SIRT regulation at the level of one enzyme or one function may be a valuable way forward to take advantage of SIRT defense properties [ 120 , 135 , 136 ].…”
Section: Sirts As Emerging Antiviral Targetsmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, the stress caused by viral replication often establishes a high NAD + -state that activates SIRTs [ 128 , 132 ]. Another approach can be based on the transcriptional functions of certain SIRTs that appear necessary for the regulation of viral gene expression [ 120 , 121 , 134 , 135 ]. Therefore, fine-tuning of SIRT regulation at the level of one enzyme or one function may be a valuable way forward to take advantage of SIRT defense properties [ 120 , 135 , 136 ].…”
Section: Sirts As Emerging Antiviral Targetsmentioning
confidence: 99%
“…SIRT1 inhibitors affect the replication and growth of many viruses including Mers-CoV, HIV, Epathitis B, Vesicular Stomatitis Virus, flu strains, adenovirus and others [ 126 , 135 , 136 , 137 , 138 , 139 ]. Notably, SIRT1 affects angiotensin-converting enzyme 2 receptor (ACE2R) expression [ 140 , 141 , 142 ].…”
Section: Sirts As Emerging Antiviral Targetsmentioning
confidence: 99%
“…The HPV E7 proteins interact with these essential cell cycle regulators, leading to the release and activation of E2F transcription factors that regulate S phase genes… E6 proteins have evolved to target p53 for proteasomal-mediated degradation…This cooperative action of the high-risk E6 and E7 oncoproteins abrogates multiple cell cycle checkpoints, thereby allowing genome amplification whilst ensuring the continued survival of the infected cell… E6 induces the hTERT promoter via interactions with c-Myc and NFX-1 proteins and contributes to cellular immortalization…” [ 171 ]. The disruptions of cell cycle control by E6 and E7 proteins lead to mitotic errors and activate cellular DNA repair functions, whose expression is necessary to enable viral replication [ 171 , 172 , 173 , 174 , 175 , 176 ]. HPV replication specifically requires the homologous recombination functions RAD51 and BRCA1 [ 177 , 178 ], even though it has been reported that E6 and E7 “impair the homologous recombination pathway” [ 179 ].…”
Section: The Importance Of Cell Type or Virus Infection History Inmentioning
confidence: 99%
“…The disruptions of cell cycle control by E6 and E7 proteins lead to mitotic errors and activate cellular DNA repair functions, whose expression is necessary to enable viral replication [ 171 , 172 , 173 , 174 , 175 , 176 ]. HPV replication specifically requires the homologous recombination functions RAD51 and BRCA1 [ 177 , 178 ], even though it has been reported that E6 and E7 “impair the homologous recombination pathway” [ 179 ].…”
Section: The Importance Of Cell Type or Virus Infection History Inmentioning
confidence: 99%
“…El ciclo de vida del VPH comienza con la infección a la capa basal del epitelio, a través de microabrasiones que alteran la barrera epitelial [14,15]. Para garantizar su persistencia, el VPH necesita infectar células basales con características de células madre que tengan la capacidad de proliferación, como ocurre en los epitelios de transición en la unión exo-endocervical y ano-rectal [1].…”
Section: Historia Natural De La Infecciónunclassified